Bahasa Orang-Orang Mandala: Relasi Bahasa antara Lontar Sunda dengan Bahasa Orang Baduy - Hady Prastya (Manuskripta, 2026)
This paper examines the relationship between the language of ancient Sundanese texts and the language of the Baduy people, especially their oral tradition of carita pantun. Although the Baduy people have a distinctive cultural style and way of life, including language, based on field evidence, the interaction between the Baduy people and people outside the Baduy community occurs dynamically. The assumption that the Baduy people isolate themselves, which is often expressed by many researchers, is clearly an unproven accusation. Because of the relationship between the language of ancient Sundanese texts and the language of the Baduy people, the question arises whether the language in the texts referred to as ancient Sundanese is chronologically related to what is called modern Sundanese or whether this language is a language variety used by certain groups. === Tulisan ini mengulas mengenai pertautan antara bahasa dalam teks Sunda kuna dengan bahasa orang Baduy terutama tradisi lisan mereka carita pantun. Meski orang Baduy memiliki corak budaya dan pranata hidup yang khas, termasuk bahasa, dari bukti di lapangan interaksi orang Baduy dan orang di luar komunitas Baduy terjadi secara dinamis. Anggapan bahwa orang Baduy mengisolasi diri, yang sering diutarakan banyak peneliti, jelas merupakan tuduhan yang tidak terbukti. Oleh karena pertautan antara bahasa teks Sunda kuna dan bahasa orang Baduy, maka timbul pertanyaan apakah bahasa dalam teks yang disebut Sunda kuna berkaitan secara kronologis dengan yang disebut bahasa Sunda modern ataukah bahasa ini merupakan salah satu ragam bahasa yang digunakan oleh kalangan tertentu.